Evaluación de prácticas agronómicas en la producción sostenible de arroz en siembra directa - Herrera, Cristian; Pineda, Marcela; Achipis, Jan; Alvarez, Maria Fernanda (2024)
The conventional rice production system includes certain agronomic practices that have a negative impact on the conservation of non-renewable natural resources, such as soil and water. Agronomic practices such as intensive soil tillage, inefficient irrigation, excessive use of agrochemicals, and continuous rice-on-rice cropping contribute to the depletion of these resources. This study evaluates the effect of different agronomic practices on soil and water conservation in the direct seeding rice system. Two study areas with contrasting production histories (rice-rice and sugarcane-maize) were selected, and four rice plantings were conducted over two years. Measurements were taken for various soil variables, such as bulk density, penetration resistance, chemical analysis, organic matter content, and total carbon, as well as water variables, including total usage per cycle, accumulated precipitation, and irrigation frequency.